A review of permanent marking for radiotherapy in the UK. Issue 1 (February 2020) - Townend, C.; Landeg, S.; Thorne, R.; Kirby, A.M.; McNair, H.A.
Abstract: Introduction: This paper presents the results of a survey of the routine use of permanent marks for radiotherapy in the UK. This was undertaken to provide an overview of current practice. Permanent marks are a somewhat invasive procedure, and should be subject to scrutiny and judicious application. Method: The authors reviewed the literature on international radiotherapy permanent marking practice. Common themes that emerged were the psychology of permanent marking and ink-type considerations, current practice and training, and safety. These were used to develop a questionnaire in order to form an overview of the use of marks nationally, and to identify any recurrent issues. The questionnaire also sought information regarding locations and numbers of permanent marks used for common treatment sites. The survey was sent to 71 departments in the UK using email. Results: 70% of departments responded. 62% of departments reported patients who had refused permanent marks. The reasons for refusal varied. India or drawing ink was used in 49 of the 51 departments (96%). The most common teaching method of tattooing involved combined observation and verbal coaching. Most departments had a written procedure for tattooing, but some did not. Although sharps injuries were rare, they were documented. Conclusion: Most departments in the UK had encountered patient refusal of permanent marks, with breast patients representing the largest group which declined. There is variation in practice throughout the UK, and the equipment used is not specialised for tattooing purposes. Sharps injuries, although rare, do occur, and training methods are not consistent. Implications for practice: The requirement for national guidelines is posited. Further investigation into the need for permanent marks in an era of state-of-the-art imaging technology is also required.